Therapy online : a practical guide - Anthony, Kate.; Nagel, DeeAnna Merz. (new delhi SAGE, 2010)
"The plethora of online services now available has led to a growing demand for practitioners to look beyond traditional face-to-face therapy and take advantage of the flexibility which email and the Internet can offer them and their clients. The guide gives up-to-the minute information and research, ethical and legal advice, on the practicalities of setting up or joining a service, and the essential therapeutic skills needed to be an effective online therapist."--pub. desc.
1 Theoretical Aspects of Online Therapy -- 2 Essential Skills and Considerations of Online Therapy -- 3 Working Without a Physical Presence -- 4 Ethical Considerations -- 5 The Business of Online Therapy -- 6 Case Study -- 7 Training Online Therapists -- 8 Supervision, Research and Groups-Couples -- 9 A Look to the Future and Concluding Thoughts.
includes bibliographic index
Includes bibliographical references and index.
Keywords: Internet in psychotherapy; Psychotherapy -- methods; Online Systems -- organization & administration; Professional-Patient Relations; Remote Consultation; Internet; Psychotherapeutische Beratung